Prestige and gender role ideology: a study of young Tanzanian men - Alexander M. Ishungisa; Joseph A. Kilgallen; Elisha Mabula; Charlotte O. Brand; Mark Urassa; David W. Lawson (Evolutionary Human Sciences)
With the objective of informing theoretical accounts of social learning and gendered conflict, we explore the role of prestige in the formation of men’s beliefs about gender in a semi-rural but fast urbanizing community in north-western Tanzania. Using focus groups and participant observation, we contrast the extent to which young men view elders and men from the neighbouring city as prestigious, and the beliefs they ascribe to each category. Elders were viewed as prestigious because of their age and position as preservers and teachers of societal norms. Their prestige was culturally mandated, as evidenced by customs bestowing respect. In contrast, only subcategories of city men were deemed prestigious dependent on individual achievement. Prestige was difficult to distinguish from dominance, as both elders and city men can exert penalties on those with differing views. Elders were viewed as mostly, but not always, unsupportive of women’s empowerment, whereas city men were viewed as mostly, but not always, supportive of women’s empowerment. We conclude that urbanization shifts the distribution of prestige, exposing individuals to novel sources of social influence. However, future studies should be wary not to oversimplify elders as upholders of patriarchal beliefs and city men as universally supportive of women’s empowerment.